Construct Validation of Five Love Languages - Edwin Adrianta Surijah; Yashinta Levy Septiarly (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2016)
Five Love Languages (FLL) is a theory proposed by Chapman (2010) about five ways a person feel most loved. This study was based on a lack of empirical evidence supporting the construct. Therefore, it aimed to validate five love languages and the results of this study were expected to be an empirical evidence to support Chapman’s idea. A Likert scale was constructed and tested toward 400 participants (148 males, 252 females; Mage = 19.85 years, SDage= 1.51 years). The FLL scale showed a promising composite reliability score ( .884) and satisfying item-total correlations (averagely > .250). Statistical analyses showed that there were 17 valid items in the Five Love Languages Scale. Confirmatory factor analysis supported the five factors in Chapman’s initial proposal.